Ideal site for buccal shelf bone mini-screw placement: a retrospective study on CBCT - Martina Horodynski; Adriana AssuntaDe Stefano; Giulia Caporro; Luciano Pacifici; Gabriella Galluccio (Annali di Stomatologia)
Objective: The aim was to determine the suitable sites of the mandibular buccal shelf (MBS) for the insertion of orthodontic mini-screws evaluating correlations between divergence and bone component and between divergence and inferior alveolar nerve (I.A.N.). Materials and Methods: The sample consisted of 93 Cone Beam Computed Tomography (CBCT). Hard tissues’s study has analysed buccal total thickness, apico-coronal total bone depth and cortical coronal bone depth. The I.A.N.’s study analyzed height and buccal thickness and distance between I.A.N. and mini-screw. Results: Cortical depth at 4 mm and 6 mm showed significant measurements. The total thickness analysis at 6 mm didn’t found difference while at 4 mm was significant for normodivergent in R7D and R7M. The bone height from I.A.N was higher in hyperdivergent at R7D and R6D. The thickness of the bone was significant in hypodivergents at L7D and R7M. The distance between I.A.N. and miniscrew was significant in L7M. Conclusions: The MBS offered adequate quantity and quality of bone for the insertion of mini-screws. The optimal site is the buccal bone at distal root of the second molar at 4 mm buccal to the cementoenamel junction (CEJ). The study showed no significant correlation between divergence and bone thickness. The bone height between the bone ridge and the roof of I.A.N. decreases progressively in the distal direction. Although hyperdivergent patients showed a greater height between the bone crest and I.A.N. in MBS, this variability isn’t clinically significant.